Effect of carbon on the microstructure and element distribution in Ti42Al5Mn alloy. Issue 17 (21st November 2020) - Tang, Hongjian; Li, Xiaobing; Xing, Weiwei; Ma, Yingche; Chen, Bo; Liu, Kui; Xia, Yuanhua; Lin, Kun
Abstract : The role of C on microstructure and local chemical composition of an as-cast Ti42Al5Mn alloy was systematically characterised. Results show that C is enriched in α2, less dissolved in γ but depleted in β o phase. Crossing the C-solubility limit, approximately 0.3 at. %, leads to the precipitation of h-type carbides (Ti2 AlC). Furthermore, a correlation between the lattice site preference and the C-solubility is rationalised by neutron powder diffraction technique, suggesting that Mn tends to substitute the position of Al site within the γ -phase (L10 -lattice) with an occupancy rate of 4.31%. Consequently, fewer Ti6 -type sites are formed where C is preferentially located. Finally, the interlamellar spacing and phase evolution as well as the preferential distribution of alloying elements are also evaluated.